Ta'á¹¡Ä«r al-WasÄ«lah at-TaÊ¿lÄ«miyyah at-TafÄÊ¿uliyyah fÄ« Tarqiyah MafhÅ«m at-TarÄkÄ«b an-Naá¸¥wiyyah - Yarda, Ulfa Fauziah; Hayati, Hayati; Arsya, Fajriyani (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The problems in this research are that the students lack enthusiasm in learning grammatical structures, and the teacher did not use excellent and engaging learning media. So the students got bored and did not understand grammatical structures except a little, and most of them still felt that grammatical structures were the most challenging lesson. The research aims to show the use of interactive learning media in upgrading the concept of grammatical structures for the eighth-grade students at the Governmental Islamic Middle School 6 Agam. The writer used experiment research to consider the effect of interactive learning media on understanding grammatical structures. The population in this research is all eighth-grade students in the Governmental Islamic Middle School 6 Agam. The eighth grade consists of seven classes, and the writer takes the sample by Purposive Sampling. The research tools are observation, interview, and test. The research analysis used the t-test rule. The mean score for the post-test in the experimental class is 67,12. The mean score for the post-test in the control class is 60,44. The writer found that the result of the t count (2,049) and the t tableÂ  (1,670), so the impact of the t count is more significant than the result of the t table. The difference between them means 0.379. The writer takes the conclusion that there is an effect of the interactive learning media in upgrading the concept of grammatical structures for the eighth-grade students at the Governmental Islamic Middle School 6 Agam. Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø£Ù†Ù‡ Ù‚Ù„Ø© Ø§Ù„ØÙ…Ø§Ø³ Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ©ØŒ ÙˆÙ„Ù… ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ù…Ø¹Ù„Ù‘Ù…Ø© Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ø¬ÙŠØ¯Ø© ÙˆØ§Ù„Ù…Ù…ØªØ¹Ø©ØŒ ØØªÙ‰ ÙŠÙ…Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙˆÙ„Ù… ÙŠÙÙ‡Ù…ÙˆØ§ Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ© Ø¥Ù„Ø§ Ù‚Ù„ÙŠÙ„Ø§ ÙˆÙ…Ø¹Ø¸Ù…Ù‡Ù… Ù„Ø§ ÙŠØ²Ø§Ù„ÙˆÙ† ÙˆÙŠØ´Ø¹Ø±ÙˆÙ† Ø£Ù† Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ© Ø£ØµØ¹Ø¨ Ø§Ù„Ø¯Ø±Ø³. Ø£Ù…Ø§ Ø£ØºØ±Ø§Ø¶ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù„Ø¨ÙŠØ§Ù† Ø§Ø³ØªØ¹Ù…Ø§Ù„ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…ÙÙ‡ÙˆÙ… Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© 6 Ø¢ØºØ§Ù…. Ø§Ø³ØªØ¹Ù…Ù„Øª Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø§Ù„Ø¨ØØ« Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ù„ØªÙ†Ø¸Ø± ØªØ£Ø«ÙŠØ± Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ø¹Ù„Ù‰ ÙÙ‡Ù… Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ©. ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ ÙƒÙ„ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© 6 Ø¢ØºØ§Ù…. ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† ÙŠØªØ±ÙƒØ¨ Ø¥Ù„Ù‰ Ø³Ø¨Ø¹Ø© ÙØµÙˆÙ„ØŒ ÙˆØªØ£Ø®Ø° Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø§Ù„Ø¹ÙŠÙ†Ø© Ø¨Ø·Ø±ÙŠÙ‚Ø© Purposive Sampling. Ø£Ù…Ø§ Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© ÙˆØ§Ù„Ø§Ø®ØªØ¨Ø§Ø±. ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ØØ« Ù‚Ø§Ø¹Ø¯Ø© Ø§Ø®ØªØ¨Ø§Ø± "Øª". Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ù„Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ù‡ÙŠ 67ØŒ12. Ø£Ù…Ø§ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ù„Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø· Ù‡ÙŠ 60ØŒ44. ÙˆÙˆØ¬Ø¯Øª Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø£Ù† Ù†ØªÙŠØ¬Ø© ØªØ§Ø¡ Ø§Ù„ØØ³Ø§Ø¨ (2ØŒ049) ÙˆØªØ§Ø¡ Ø§Ù„Ø¬Ø¯ÙˆÙ„ (1ØŒ670) ÙÙ†ØªÙŠØ¬Ø© ØªØ§Ø¡ Ø§Ù„ØØ³Ø§Ø¨ Ø£ÙƒØ¨Ø± Ù…Ù† Ù†ØªÙŠØ¬Ø© ØªØ§Ø¡ Ø§Ù„Ø¬Ø¯ÙˆÙ„. Ø§Ù„ÙØ±Ù‚ Ø¨ÙŠÙ†Ù‡Ù…Ø§ ÙŠØ¹Ù†ÙŠ 0ØŒ379. ÙˆØªØ£Ø®Ø° Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø§Ù„Ø®Ù„Ø§ØµØ© Ø¨Ø£Ù† ÙŠÙˆØ¬Ø¯ ØªØ£Ø«ÙŠØ± Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…ÙÙ‡ÙˆÙ… Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„Ù†ØÙˆÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© 6 Ø¢ØºØ§Ù….